Effect of fuel injection strategies and EGR on biodiesel blend in a CRDI engine. (15th August 2019) - Bhowmick, Pathikrit; Jeevanantham, A.K.; Ashok, B.; Nanthagopal, K.; Perumal, D. Arumuga; Karthickeyan, V.; Vora, K.C.; Jain, Aatmesh
Abstract: Biodiesel appears as a replenishable and sustainable energy source and can be used a direct replacement to petro-diesel without any major transformations in ongoing diesel engines. This work concentrates on production of Calophyllum Inophyllum biodiesel (CIB) and preparing 10% blend (CIB10) sample to investigate the effects of varying the injection strategies and exhaust gas recirculation (EGR) in common-rail direct injection engine. The experimental results shows that 10% of pilot fuel and 90% main injection strategy (B10@P10-M90) is superior among all others injection strategies with respect to pure diesel. B10@P10-M90 fuel injection strategy produces the maximum efficiency of 35.8% and lowest fuel consumption of 0.25 kg/kWh compared to all the injection strategies. The carbon monoxide (CO) and hydrocarbon (HC) emissions are also found to be quite low compared to all the other test samples including pure diesel. However B10@P10-M90 results in higher average oxides of nitrogen (NOx ) emission which is 18.9% higher in contrast to conventional diesel at full load condition. With the implementation of 10% and 20% EGR with B10@P10-M90, the average NOx emissions decreased by 14.4% and 27.6% respectively compared to B10@P10-M90 without any EGR without significant loss in the performance of the existing diesel engine. Highlights: Calophyllum Inophyllum biodiesel is extracted and utilized in CRDi engine. Engine parameters such as injection strategies and EGR was investigated. Efficiency is increased and fuel consumption is reduced for the CIO blend. Better combustion characteristics were obtained by varying the injection strategies. Reduction in HC, CO and smoke emissions were observed for injection strategies.